Determination of toxic, trace and minor elements content in local Kurdish yoghurt samples - Ibrahim, Kocher Jamal; Qaisar, Shaimaa Ahmed; Al-Saadi, Jasim Mohammed Salah (Sulaimani Journal for Pure and Applied Sciences, 2018)
The concentrations of toxic , minor and trace elements in local Kurdish yoghurt samples collected from different markets in Halabja governorate ,Kurdistan region ,Iraq were determined in this study. Results indicated that Aluminum (Al), Titanium (Ti) and Lead (Pb) have the highest concentration among other toxic trace elements in yoghurt samples. The concentration of these elements were 523.34 - 106.1, 438 - 325 and 4.36 – 0.4 µg kg-1 for Al, Ti and Pb respectively. Concentrations of trace elements Be, V, Li, Cs and Co in local yoghurt samples were 16.63 – 2.32 , 1.33 - 0.02, 11.71 - 0.83 ,13.3 - 0.18 and zero µg kg-1 respectively . Zinc had the highest value among other miner elements in yoghurt samples .Zn concentration found in local yoghurt was between 5807.99 – 20945.1 μg.kg-1.
Keywords: Yoghurt; Minor elements; Toxic elements; Trace elements